Microparticle manipulation by a four-spiral electrode microstructure - Julio Enrique Duarte, Joseph Samitier Marti, Flavio Humberto Fernández Morales, (Universidad Pedagógica y Tecnológica de Colombia, 2010)
The focus of attention of this paper is to explain the operation of a four-spiral electrode microstructure, wholly developed in CMOS technology, that has been designed to achieve linear motion of microparticles. This device makes good use of the travelling wave dielectrophoresis (TWD) phenomenon and is affected by the electrohydrodynamic (EHD) effects. Numerical simulations were carried out by means of the Finite Element Method to assess the particle behaviour. The microsystem was tested employing polystyrene microspheres of 6 mm in diameter.